Construction of mathematical models of the human operator - Гусак, Олена Михайлівна (Technology audit and production reserves, 2015)
In this article the human operator is considered as a unit, has a certain "transfer function" in a similar way to unit that used in communication theory. Such assumption is a certain degree of approximation, but this formalization allows us to justify the fact that the systems described in the study are subject to the volume and speed of receiving the information, the speed of processing and decision-making, and, finally, the capacity of the "exit" – the speed of the motor corresponding reactions. Presented principles and methods of analysis of operator activity are based on the theory of automatic control and are a continuation of research on the construction of a mathematical model of human operator. Development of analysis principles of the operators of automated systems, the identification of its specific features, structural features and psychological content needed to address a number of practical issues that arise in the design of control systems. These include: the optimal organization of operator activities, development of adequate and effective methods of teaching of operator personnel, the principles of its selection for those activities in which even a small operator error could result in serious accidents that result in the destruction of expensive equipment and loss of life (for example, in military systems).